Penile sparing surgical approaches for primary penile tumors: preserving function and appearance - Baumgarten, Adam S.; Fisher, John S.; Lawindy, Samuel M.; Pavlinec, Jonathan G.; Carrion, Rafael E.; Spiess, Philippe E. (Translational Andrology and Urology; Vol 6, No 5 (October 26, 2017): Translational Andrology and Urology (Management of Penile Cancer), 2017)
Penile cancer is a rare and potentially disfiguring disease. There are multiple treatment options for primary penile lesions. Penile sparing approaches offer an attractive option as they can provide several quality of life benefits without detrimental oncologic outcomes. With appropriate diagnostic evaluation and staging, penile sparing techniques provide proper cancer control with improved cosmetic and functional results. Regardless of the chosen treatment modality, a commitment to close follow-up remains a critical component of all treatment considerations. The goal of this review is to provide an overview of the multiple treatment strategies for primary penile tumors with a focus on penile sparing surgical approaches.